Analisis Kepercayaan Pasien Rawat Inap pada RSUD di Propinsi Kepulauan Riau - Hadiyati, Hadiyati (Komunitas Manajemen Kompetitif, 2015)
Abstract: Speaking of health problems, this is a form of investment for the community, because health is a basic capital that is needed by all people to be able to move in accordance with the duties and responsibilities of each. Hospital patient requires trust, trust is a behavior in which leads to an assessment of a given action or attitude. This belief affect the sustainability of a service that sediri. In the case of hospital services, the service becomes essential in making the patient wants and continue to use the services of the hospital. Many of the complaints and prove that the hospitals Kepulauan Riau, the most fundamental problems that need to be built is a matter of the ability of doctors daam cure the patient. Keywords: Confidence, ability, integrity and Policy